2022
DOI: 10.1186/s12887-022-03435-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and associated risk factors in a sample of adolescents in Gaborone, Botswana: a cross-sectional study

Abstract: Background Despite the high proportion of adolescents living with mental health issues in low- to middle-income countries (LMICs), especially in Botswana, there is a significant deficit of local research to guide an increase in prevention and treatment. We, therefore, aimed to assess the prevalence and associated risk factors of psychiatric disorders (PD) in a sample of secondary school students in Botswana. Methods This cross-sectional study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Youth living with HIV (YLWH) in SSA can be more likely to experience common mental disorders (CMDs), such as depression and anxiety, compared with their HIV‐negative peers (Too et al, 2021). Recent studies on the burden of CMDs on YLWH in SSA showed depression and anxiety occurred at rates of 14%–53% and 15%–25%, respectively (Dessauvagie et al, 2020; Olashore et al, 2022). YLWH are at higher risk of CMDs due to cultural stigma, neurological impacts of HIV, fear of dying from HIV and side effects of some antiretroviral therapies (ARTs) (Too et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Youth living with HIV (YLWH) in SSA can be more likely to experience common mental disorders (CMDs), such as depression and anxiety, compared with their HIV‐negative peers (Too et al, 2021). Recent studies on the burden of CMDs on YLWH in SSA showed depression and anxiety occurred at rates of 14%–53% and 15%–25%, respectively (Dessauvagie et al, 2020; Olashore et al, 2022). YLWH are at higher risk of CMDs due to cultural stigma, neurological impacts of HIV, fear of dying from HIV and side effects of some antiretroviral therapies (ARTs) (Too et al, 2021).…”
Section: Introductionmentioning
confidence: 99%